From suspected Creutzfeldt-Jakob disease to confirmed histoplasma meningitis. (7th July 2016) - Batra, Vivek; Khararjian, Armen; Wheat, Joseph; Zhang, Sean X; Crain, Barbara; Baras, Alexander
Abstract : A 77-year-old man with chronic obstructive lung disease who was on steroids, presented to the hospital after a fall with subacute headaches and ataxia. During the patient's hospital course, his clinical condition deteriorated with myoclonic jerks, fevers and severe encephalopathy. An extensive workup, including EEG, brain MRI and lumbar puncture, revealed possible Creutzfeldt-Jakob disease. Unfortunately, the patient failed to improve and died 12 days after admission. A brain-only autopsy revealed he had acute histoplasma meningitis with patchy superficial cerebritis.